Reduction of insulin signalling pathway IRS-1/IRS-2/AKT/mTOR and decrease of epithelial cell proliferation in the prostate of glucocorticoid-treated rats - Costa, Maite M. [UNESP]; Violato, Natalia M. [UNESP]; Taboga, Sebastiao R. [UNESP]; Goes, Rejane M. [UNESP]; Bosqueiro, José Roberto [UNESP] (Wiley-Blackwell, 2012)
Previous studies by our research group using a model of insulin resistance induced by dexamethasone (DEX) showed that in the rat ventral prostate there was epithelial and smooth muscle cell atrophy and there were also alterations in fibroblasts. Proteins of the insulin signalling pathway are known to be very important for cell proliferation and development. Thus, we investigated the insulin signalling pathway and epithelial proliferation in the rat ventral prostate in this model and correlated the findings with expression of glucocorticoid (GR) and androgen (AR) receptors. Insulin resistance was induced in adult male Wistar rats by injection of DEX (1 mg/kg, ip for 5 consecutive days), whereas control (CTL) rats received saline. DEX treatment resulted in a significant decrease in body weight, but not in prostate weight. Reductions in insulin receptor 1 (IRS-1) (CTL 1.11 +/- 0.06; DEX 0.85 +/- 0.03), IRS-2 (CTL 0.95 +/- 0.05; DEX 0.49 +/- 0.04), AKT (CTL 0.98 +/- 0.03; DEX 0.78 +/- 0.02), mammalian target of rapamycin (mTOR; CTL 0.65 +/- 0.08; DEX 0.22 +/- 0.05), GR (CTL 1.30 +/- 0.09; DEX 0.57 +/- 0.10) and AR (CTL 1.83 +/- 0.16; DEX 0.55 +/- 0.08) protein levels were observed in the prostate of DEX-treated rats. The expression of the IRa-subunit, phosphoinositide 3-kinase, p-AKT, p70S6K, extracellular signal-regulated kinase (ERK) and p-ERK was not altered. The frequency of AR-positive cells in the epithelium of the prostate decreased in the glucocorticoid-treated group, and the intensity of the reaction for this receptor in the cell nuclei was lower in this group. Furthermore, the treatment with DEX reduced the frequency of proliferating cell nuclear antigen-positive (PCNA) cells 30-fold. This study suggests that the reduction in the insulin signalling pathway proteins IRS-1/IRS-2/AKT/mTOR in the prostate of DEX-treated rats may be associated with the morphological alterations observed previously.
Keywords: cell proliferation; dexamethasone; insulin resistance; insulin signalling; ventral prostate